Creating Otherness: Minority Religions and Media in Lithuania. (18th June 2018) - Pocė, Gintarė; Ališauskienė, Milda
Abstract : This article contributes to the ongoing theoretical and empirical discussions within the studies of media and religion on the interaction of these social institutions in contemporary society. Firstly, we locate our research questions within the recent theoretical debates on relations between media and religion in contemporary society, the US, Western Europe and, particularly, postcommunist countries. Secondly, we discuss the representations of minority religions in Lithuanian media grounding on the empirical research of Lithuanian media in 2000-2012. Results of the empirical research showed that minority religions in Lithuanian media were represented mostly in a negative and scandalous context. The majority of articles contained various rhetorical strategies which strengthened the proposed viewpoints. Opinions of the members of minority religions, experts and society were the most common information source dealt with in the analysed articles.